Mocaf (Modified Cassava Flour)-Based Artificial Rice Production (Study of Mocaf and Rice Flour Proportion with the Addition of Porang Flour) - Yuwono, Sudarminto Setyo; Febrianto, Kiki; Dewi, Novi Sintya (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
National rice production is currently quite a lot, but feared not enough for national rice necessity. Therefore, diversification of staple foods in the form of artificial rice is needed to support national food availability. Some problems in artificial rice product are first its texture. It tends to be hard due to the high content of amylose in Mocaf. As well the strong aroma of Mocaf makes artificial rice difficult to be accepted by consumers. Also we need to use additional materials such rice and porang flour to improve its texture and taste. This research used Randomized Block Design method (RBD) with two factors. The first factor was Mocaf and rice flour proportion consisting of 3 levels (90 : 10, 80 : 20 and 70 : 30) and the second factor was the addition of porang flour consisting of 3 levels (2%, 3% and 4%). The obtained data were analyzed using ANOVA (Analysis of Variance) and then continued using Least Significant Different Test (LSD) at α = 5%. The organoleptic test data were analyzed using Hedonic Scale Scoring Test and then continued using Duncan’s Multiple Range Test (DMRT) at α = 5%, while for determining the best treatment using De Garmo effectivity index method.The best treatment based on the physical, chemical and organoleptic parameters was obtained from the treatment Mocaf and rice flour proportion = 70 : 30 with the addition of porang flour 3% resulting artificial rice with the physical and chemical characteristics as follows color brightness (L *) 50.47, texture 1.27 N, rehydration capacity 177%, volume development 125%, water content 9.21%, starch 70.83%, amylose 18.86%, ash 0.62%, fat 2.71%, protein 2.71%, carbohydrates total 84.75%, oxalic acid 0.06% and organoleptic characteristics, as follows color 3.55 (neutral), aroma 3.60 (neutral), texture 4.00 (like) and taste 3.85 (neutral).Keywords: artificial rice, Mocaf, rice flour, porang flour